The Nexus Between Vegetation, Urban Air Quality, and Public Health: An Empirical Study of Lahore - Khan, Muhammad Kaleem; Naeem, Kashif; Huo, Chunhui; Hussain, Zahid (Frontiers in Public Health, 2022)
Global climate change and the deteriorating quality of urban air are the major issues affecting the atmospheric ecosystem of Pakistan. To avoid poor monitoring and management of air pollution, improvements through the latest technologies such as GIS and remote sensing are required. This research involves spatial analysis, which discusses the impact of vegetation on air quality and public health. Data of air quality at 20 different points, showing the concentration of four pollutants, namely NOx, CO, SO2, and PM10, with mean observations for 24-h, are taken from EPA, Lahore. The results show that the concentrations of SO2, CO, and PM10 are exceptionally high at the site of the Badshahi Mosque. The analysis shows that the highest polluted areas have the lowest vegetation levels, whereas areas with low pollution concentration have more vegetation cover. Moreover, less vegetation has a higher death rate attributable to household air pollution. The study suggests that greening strategies, vegetation screens, and vegetation barriers should mitigate urban heat air pollution and minimize the air pollution attributable deaths. For pollution and vegetation monitoring, strict laws and monitoring programs must be implemented in major cities.